A membrane-permeabilizing peptide sensitizes microcin J25-resistant strains - Pomares, Maria Fernanda (2010)
Microcin J25 (MccJ25) is a plasmid-encoded, 21-amino-acid, antibacterial peptide produced by Escherichia coli. MccJ25 inhibits RNA polymerase and the membrane respiratory chain. MccJ25 uptake into E. colisensitive strains is mediated by the outer membrane receptor FhuA and the inner membrane proteins TonB, ExbB, ExbD, and SbmA. This peptide is active on some E. coli, Salmonella, and Shigella species strains, while other Gram-negative bacteria, such as clinical isolates of Enterobacter cloacae, Citrobacter freundii, Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter baumannii, Moraxella catarrhalis, and Salmonella entérica serovar Typhimurium, are completely resistant. In the present work, we demonstrated that the membrane permeabilizing peptide (KFF)3K made some resistant strains sensitive to MccJ25, among them S. Typhimurium, where the antibiotic inhibits in vitro cell growth and bacterial replication within macrophages. The results demonstrate that the membrane permeabilization induced by (KFF)3K allows MccJ25 penetration in an FhuA and SbmA-independent manner and suggest that the combination of both peptides could be considered as a therapeutic agent against pathogenic Salmonella strains.